2020
DOI: 10.1126/sciadv.aba6752
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of site-specific antibody-drug conjugates by ADP-ribosyl cyclases

Abstract: Most of the current antibody-drug conjugates (ADCs) in clinic are heterogeneous mixtures. To produce homogeneous ADCs, established procedures often require multiple steps or long reaction times. The introduced mutations or foreign sequences may cause high immunogenicity. Here, we explore a new concept of transforming CD38 enzymatic activity into a facile approach for generating site-specific ADCs. This was achieved through coupling bifunctional antibody-CD38 fusion proteins with designer dinucleotide-based cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…CD38 possesses NAD + glycohydrolase activity and ADP ribosyl cyclase activity, both of which could convert NAD + to cADPR as well as hydrolase activity that converted cADPR to ADPR [ 9 , 10 ]. The formation of cADPR and ADPR catalyzed by CD38 from NAD + are dominated by a series of amino acid residues especially Cysteine123 and Cysteine205 (for mouse) as well as glutamate146 and glutamate226 (for human) [ 11 , 12 ]. Both ADPR and cADPR are important second messengers via ryanodine receptors (RyRs) to mediate the transmembrane transport of Ca 2+ from endoplasmic reticulum in hematopoietic cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD38 possesses NAD + glycohydrolase activity and ADP ribosyl cyclase activity, both of which could convert NAD + to cADPR as well as hydrolase activity that converted cADPR to ADPR [ 9 , 10 ]. The formation of cADPR and ADPR catalyzed by CD38 from NAD + are dominated by a series of amino acid residues especially Cysteine123 and Cysteine205 (for mouse) as well as glutamate146 and glutamate226 (for human) [ 11 , 12 ]. Both ADPR and cADPR are important second messengers via ryanodine receptors (RyRs) to mediate the transmembrane transport of Ca 2+ from endoplasmic reticulum in hematopoietic cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study suggested that payload stably attached to an antibody via an NAD + analogue-based linker could be rapidly released upon cellular internalization. 25 The payload release of the PAR polymer-based ADC in cellular environment will be investigated. In addition to mechanistic studies of the degradation of functionalized PAR polymer and the drug release, future studies include systematic evaluation of pharmacokinetics, therapeutic efficacy, and toxicity of the PARylated PARP1-Fab-MMAF conjugate in comparison to established ADCs and polymer–drug conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…Covalent attachments of small-molecule drugs to functionalized PAR polymers can increase overall drug loading and solubilization, possibly expanding the spectrum of payloads for targeted delivery. Similar to ADCs with pyrophosphate diester-derived linkers, 24 , 25 PAR polymer–drug conjugates may allow to stably carry payloads in plasma and rapidly release drugs upon internalization into target cells. Collectively, PAR polymer-based ADCs may provide improved physicochemical properties, therapeutic efficacy, and safety profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al exploited these developments via fusion of the catalytic domain of CD38 to the heavy chain C-terminus or light chain N-terminus of trastuzumab. 213 Subsequent reaction of the fusion antibody Fig. 13 Non-enzymatic bioconjugation methods used to construct homogeneous ADCs at the: (A) N-terminal position, where terminal glutamate and cysteine residues can be selectively modified with aldehyde functionalised payloads, and Ser residues introduced can be oxidised to aldehydes, which can be trapped using alkoxyamine functionalised payloads to form oxime linked conjugates; (B) p-clamp peptide sequence selectively reacts with perfluoroaromatic probe, DBCO tagged antibody selectively reacts with DBCO reagents via the thiol-yne reaction, CD38 tag reacts with covalent inhibitor-tagged payload, forming a stable arabinosyl ester.…”
Section: C-/n-terminal Modificationsmentioning
confidence: 99%